Colposcopy in young and postmenopausal women in the light of the current image classification according to IFCPC 2011 - Malarewicz, Andrzej; Sola, Michał (Menopause Review/Przegląd Menopauzalny, 2013)
Bornstein et al. developed a classification which was endorsed by the Congress of the International Federation for Cervical Pathology and Colposcopy (IFCPC) held in Rio de Janeiro on 5 July 2011. The classification accepted at the Congress is aimed at considerable facilitation of efficient clinical management. The IFCPC 2011 classification of the colposcopic images, which does not change basic colposcopic definitions, is composed of two parts: a general one and a detailed one. In the general part, attention is focused on the degree to which the inspected colposcopic image is suitable for evaluation, how extensive the inspected lesion of the cervix is and whether it is visible in full or only partially. In the detailed part, the observed colposcopic images are divided into normal and abnormal ones (from an oncological point of view), implying cervical carcinoma and others. The classification distinguishes two grades of epithelial anomalies: grade 1 – low grade (low grade squamous intraepithelial lesion – LG SIL) and grade 2 – high grade (high grade squamous intraepithelial lesion – HG SIL). The basis for categorizing the epithelial lesions observed in colposcopy to the appropriate grade of the anomaly is above all the outcome of acetic acid test. The classification also clearly defines other criteria that allow to categorize the observed colposcopic images to either of the mentioned groups. In many women, as years go on following menopause, the epithelium is getting thinner and its surface is becoming more and more sleek and smooth. A thin atrophic squamous epithelium is penetrating into a cervical canal and then the border of the squamocolumnar junction occurs deeply in the canal. It is necessary, according to suggestions of Carcopino et al., to collect a cytological swab from the interior of the canal or curette carefully the canal and perform a histopathological assessment of the collected material. An Addendum containing the abnormal epithelial lesions of the uterine cervix is attached to the IFCPC 2011 classification of colposcopic images. It refers to the procedures of collecting tissue material from the cervix. The  Addendum defines also the sizes of collected tissue samples.